Factors affecting retention of the members of the linden of Seventh- Day Adventists Church in New York - Donovan Antonio Lauther (Anuario de Investigación UM, 2020)
The empirical model in which pastoral leadership, church programs, interpersonal relationships, support, facility amenities are predictors of retention as per-ceived by members of the Linden Seventh-day Adventists Church located in Queens, New York, USA.